Testing for boosting at the Paralympic games: policies, results and future directions. Issue 13 (16th May 2013) - Blauwet, Cheri A; Benjamin-Laing, Harry; Stomphorst, Jaap; Van de Vliet, Peter; Pit-Grosheide, Pia; Willick, Stuart E
Abstract : Background: 'Boosting' is defined as the intentional induction of autonomic dysreflexia (AD) by athletes with a spinal cord injury (SCI) at or above the level of T6 for the purpose of improving sports performance. Boosting has been shown to confer up to a 9.7% improvement in race time. Additionally, to compete in a hazardous dysreflexic state, whether intentional or unintentional, would present an extreme health risk to the athlete. For these reasons, the International Paralympic Committee strictly bans the practice of boosting, and has developed a protocol to test for its presence. Methods: Testing was performed at three major international Paralympic events. Education regarding the dangers of AD was provided to athletes and team staff. Testing was conducted on athletes from the relevant sport classes: Athletics (wheelchair racing classes T51/T52/T53) and Handcycling (H1). Key parameters included the athlete's demographics (gender, country of origin), classification and blood pressure measurements. An extremely elevated blood pressure was considered to be a proxy maker for AD, and a systolic blood pressure of ≥180 mm Hg was considered a positive test. Results: A total of 78 tests for the presence of AD were performed during the three games combined. No athlete tested positive. The number of athletes tested, by classification, was: 6 in Athletics T51, 47 in Athletics T52, 9 in Athletics T53 and 16 in Handcycling H1. Of those tested, the average systolic and diastolic blood pressures were 135 mm Hg (range 98–178) and 82 mm Hg (range 44–112), respectively. All athletes were compliant with testing. No athletes were withdrawn from competition due to the presence of AD. Discussion: Testing for the presence of AD in paralympic athletes with SCI prior to competition has been carried out for the first time at three major international paralympic competitions. There have been no positive tests thus far. Knowledge gained during these early testing experiences will be used to guide ongoing refinement of the testing protocol and the development of further educational initiatives.